2007
DOI: 10.1021/jf062643p
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on the Release of Aroma Compounds from Structured and Nonstructured Oil Systems Using Proton-Transfer Reaction Mass Spectrometry

Abstract: Relative retention, volatility, and temporal release of volatile compounds taken from aldehyde, ester, and alcohol chemical classes were studied at 70 degrees C in model systems using equilibrium static headspace analysis and real time dynamic headspace analysis. These systems were medium-chain triglycerides (MCT), sunflower oil, and two structured systems, i.e., water-in-oil emulsion and L2 phase (water-in-oil microemulsion). Hydrophilic domains of the emulsion type media retained specifically the hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
(40 reference statements)
3
26
0
Order By: Relevance
“…In addition, the headspace concentration of limonene above the gels is similar evidencing that the gels, even if showing different in structure, affect the aroma partition in the same manner. Results are in agreement with those reported by Landy et al (2007), who found aroma retention in emulsions containing lamellar phases of unsaturated monoglycerides. The decrease in the headspace concentration of aroma compounds of gelled systems was also found in gels containing other hydrocolloids such as proteins, pectins and polysaccharides (Karaiskous, Blekas, & Paraskevopoulou, 2008;Monge, Negri, Giacomazza, & Bulone, 2008;Renard, van de Velde, & Visschers, 2006).…”
Section: Aroma Releasesupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the headspace concentration of limonene above the gels is similar evidencing that the gels, even if showing different in structure, affect the aroma partition in the same manner. Results are in agreement with those reported by Landy et al (2007), who found aroma retention in emulsions containing lamellar phases of unsaturated monoglycerides. The decrease in the headspace concentration of aroma compounds of gelled systems was also found in gels containing other hydrocolloids such as proteins, pectins and polysaccharides (Karaiskous, Blekas, & Paraskevopoulou, 2008;Monge, Negri, Giacomazza, & Bulone, 2008;Renard, van de Velde, & Visschers, 2006).…”
Section: Aroma Releasesupporting
confidence: 93%
“…Vauthey, Visani et al (2000); Vauthey, Milo et al (2000) have shown that systems composed of 80% unsaturated monoglyceride and 20% water, in which the polar lipids organized in the cubic phase, display weaker aroma retention capability than a water-in-oil emulsion containing 80% of triglycerides. On the contrary, Landy et al (2007) found an increase in aroma retention of lipophilic compounds in a system (30% unsaturated monoglycerides; 60% triglycerides; 10% water) containing the lamellar phase of unsaturated monoglycerides. Finally, Phan et al (2008) studied the aroma retention properties of aroma compounds from the dispersed phase of self-assembly structures formed by unsaturated monoglycerides in an emulsified water solution.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Most Table 13.1 Air/water and air/oil partition coefficients at 25 C (Buttery et al, 1965;Guichard, 2006;Landy et al, 2007) of the proteins used as food ingredients for different applications (such as gelation, thickening, emulsification and foaming) adopted a globular structure that results from an equilibrium between physico-chemical parameters including hydrophobic interactions, electrostatic interactions, hydrogen bonding, van der Waals forces and configurational entropy (McClements, 2002). The structure tends to reduce the contact area between non-polar groups and water and, for this reason, the main driving force stabilising the compact structure of globular proteins is related to hydrophobic interactions.…”
Section: Protein Structure In Relation To Aroma Bindingmentioning
confidence: 99%
“…Lipid polymorphism is an essential aspect to consider in designing liposomes for biologically active agent delivery (Landy et al 2007). For example, a lamellar phase comprising parallel strands of DNA sandwiched between fluid lipid bilayers is a prevailing system for DNA packaging (Schmutz et al 1999), and the subsequent induction of a phase transition from the multi-lamellar 'sandwich' structure to an inverted hexagonal or cubic phase is associated with the efficient release of DNA molecules (Koynova et al 2005).…”
Section: Introductionmentioning
confidence: 99%